Computerization in the consumer goods manufacturing sector of Philippine industry - Chan, Anna Katharyna C.; de Castro, Ma. Paz Trinidad V.; Gervasio, Melinda T.; Sinense, Ma. Estrella Bernardita P. (College of Engineering, 1986)
Computerization in the consumer goods manufacturing sector is still in its introductory stage. Very few companies are using process computers, although most have already started integrating small computerized systems into their operations. At this stage, overall reactions to the new systems have been favorable, which can be partly attributed to the manner in which people were introduced and allowed to adjust to the computers. The trend among manufacturers is towards further computerization, even if it is still too early to tell whether the inital systems are meeting their objectives.